Testing the Reliability of Sedimentary Paleomagnetic Datasets for Paleogeographic Reconstructions - Dallanave, Edoardo; Kirscher, Uwe (Frontiers in Earth Science, 2020)
Paleogeographic reconstructions largely rely on paleomagnetic data, mostly in the form of paleomagnetic poles. Compilations of poles are used to determine so called apparent polar wander paths (APWPs), which capture the motion through time of a particular location with respect to an absolute reference frame such as the Earth’s spin axis. Paleomagnetic dataset from sedimentary rocks are particularly relevant, because of their spatial distribution and temporal continuity. Several criteria have been proposed through the years to assess the reliability of paleomagnetic datasets. Among these, the latitudinal-dependent elongation of a given paleomagnetic directions distribution, predicted by a widely accepted paleosecular variations model, has been applied so far only to investigate inclination flattening commonly observed in sedimentary rocks. We show in this work that this concept can be generalized to detect “contamination” of paleomagnetic data derived from tectonic strain, which is not always detected only by field observation. After generating different sets of simulated geomagnetic directions at different latitudes, we monitored the variations in the shape of the distributions after applying deformation tensors that replicate the effect of increasing tectonic strain. We show that, in most cases, the "deformation" of the dataset can be detected by elongation vs. inclination ratios not conforming to the values predicted by paleosecular variations models. Recently acquired paleomagnetic directions and anisotropy of magnetic susceptibility (AMS; a parameter very sensitive to tectonic strain) data from New Caledonia verifies the results of these simulations and highlights the importance of measuring AMS when using sedimentary paleomagnetic data for paleogeographic reconstruction. We suggest to include AMS measurement and distribution shape analysis to assess sedimentary paleomagnetic data used for paleogeographic reconstructions.